Dronitaly the event for Unmanned Vehicle System in Milan (GEOmedia, 2015)
Dronitaly is the event dedicated to all Unmanned Vehicle Systems (aerial, aquaticor land) that unites the leading names in professional remotely piloted systemsmarket: producers, distributors, aeronautical operators, service providers, flying schools, universities, institutions, regulatory authorities, associations and the media.